2021
DOI: 10.1108/ijcs-07-2020-0014
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric analysis of sharing economy logistics and crowd logistics

Abstract: Purpose This study aims to review the literature on sharing economy logistics and crowd logistics to answer the three following questions: How is the literature on sharing economy logistics structured? What are the main trends in sharing economy logistics and crowd logistics? What are the future research options? Design/methodology/approach Bibliometric analysis is used to evaluate 85 articles published over the past 12 years; it identifies the top academic journals, authors and research topics contributing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 91 publications
0
7
0
2
Order By: Relevance
“…In addition to the cloud services, ref. [45] argued that crowd logistics companies could mediate the relationship between LSPs and their clients by hosting the outsourcing services through various technologies to allow sharing of information to optimize logistics operations. Thus, to meet customers' needs, LSPs are accelerating the adoption of relevant information technologies [42].…”
Section: Technology In Logistics Outsourcingmentioning
confidence: 99%
“…In addition to the cloud services, ref. [45] argued that crowd logistics companies could mediate the relationship between LSPs and their clients by hosting the outsourcing services through various technologies to allow sharing of information to optimize logistics operations. Thus, to meet customers' needs, LSPs are accelerating the adoption of relevant information technologies [42].…”
Section: Technology In Logistics Outsourcingmentioning
confidence: 99%
“…Crowd-logistics refers to logistics services that tap into the logistics resources and capabilities of individuals, using mobile applications and web-based platforms (Carbone et al, 2017). Most of the research in this literature focuses on the optimization of matching or geo-localization algorithms and elaborates models to enhance the logistics performance of the crowd, especially in last-mile delivery (Saglietto, 2021). Other articles provide a comprehensive analysis of crowd-logistics business models (e.g.…”
Section: Research On Crowd-logistics: Optimization and Categorizationmentioning
confidence: 99%
“…, 2017). Most of the research in this literature focuses on the optimization of matching or geo-localization algorithms and elaborates models to enhance the logistics performance of the crowd, especially in last-mile delivery (Saglietto, 2021). Other articles provide a comprehensive analysis of crowd-logistics business models (e.g.…”
Section: Sharing Economy Literature: Highlights From a Supply Chain P...mentioning
confidence: 99%
“…Furthermore, the sharing economy contributes to workforce exchanges by using online apps or platforms (Belanche et al, 2021). From an extensive review of the literature on sharing economy for logistics services and crowd shipping, Saglietto (2021) showed that the literature focus on the optimal allocation of costs, prices and supplier relationships. Moreover, the author lists the international practices and reports the environmental impact of urban freight transport and crowd shipping.…”
Section: Introductionmentioning
confidence: 99%